Cybersecurity regulations in the water sector - level of cybersecurity maturity in the Portuguese water sector - Kührer, Samuel Darius (2022)
Cyber-attacks are a massive threat for publicorganizations in the water sector. Protecting sensitive data and securing plants or technological assets are on the top priority list of governments worldwide. To advance this critical field of research, this study examined the Portuguese water sector's cybersecurity maturity based on the cybersecurity maturity assessment framework (CMAF). The outcome of this study highlights the unformalized level of maturity and the lack of cybersecurity measures implemented in the Portuguese water sector. Limiting factors and interdependencies between different cybersecurity focus areas are identified, providing recommendations for the water utility and other critical sectors.